Investigate The Level of Technical Knowledge of Adults Towards Children Restraint System at Batu Pahat - Maxtherson Usah anak Ngadan; Nursitihazlin Binti Ahmad Termida (Recent Trends in Civil Engineering and Built Environment, 2021)
Accident rates in Malaysia are among the highest in Southeast Asia. Therefore, the Malaysian government has decided to make it mandatory for all types of vehicles to install a child safety seat or child restraint system (CRS) starting January 1st, 2020. The installation of this CRS is mandatory for vehicle owners with children under 11 years old. The main function of this CRS is to reduce the impact of strong vibration during accidents. To ensure that this system is able to act effectively and efficiently, this CRS has been divided into several types according to age, seat position in the vehicle, child weight and child height. Therefore, all vehicle owners should take into account several important factors to maximize the effectiveness of the system. This study was conducted to determine the level of technical knowledge of adults related to CRS and also to investigate the relationship between their levels of technical knowledge related to this system with the selection of the correct type of CRS. The selection factor of this system is very important because it can affects the level of injury suffered by children during accidents. A total of 382 adults age 18 and above were selected around Batu Pahat. The results of the study found that the level of technical knowledge of users related to CRS is high in which the average value of the score is 3.7148. The results of the Chi-square test found that the level of technical knowledge of the respondents related to CRS affects the selection of the correct type of CRS with the value of 163.875.